A review of bioactive plant polysaccharides: Biological activities, functionalization, and biomedical applications. Issue 1 (January 2015) - Liu, Jun; Willför, Stefan; Xu, Chunlin
Abstract Natural polysaccharides from different sources have long been studied and widely used in different areas, such as food and feed, medicine and pharmaceutics, and in papermaking. In recent decades, there has been an increased interest in the utilization of polysaccharides, particularly bioactive ones, for various novel applications owing to their biocompatibility, biodegradability, non-toxicity, and some specific therapeutic activities. The main goal of this paper was to review the sources, natively biological activities, isolation, characterization, and the structural features of natively bioactive polysaccharides. Moreover, the article has also been forcused on the chemical/chemo-enzymatic functionalizations that may create novel opportunities to maximally exploit the various valuable properties of polysaccharides, particularly from wood species, in previously unperceived applications especially for biomedical applications, such as tissue engineering, wound healing, and drug delivery. This article was to review novel strategies to tailor functional materials with above mentioned application potentials for the polysaccharides from wood species.